Pre-feasibility study of supply systems based on artificial drying of delimbed stem forest chips - Laitila, Juha; Ahtikoski, Anssi; Repola, Jaakko; Routa, Johanna (Silva Fennica, 2017)
This study was aimed at determining the maximum cost level of artificial drying required for cost-efficient operation. This was done using a system analysis approach, in which the harvesting potential and procurement cost of alternative fuel chip production systems were compared at the stand and regional level. The accumulation and procurement cost of chipped delimbed stems from young forests were estimated within a 100 km transport distance from a hypothetical end use facility located in northern Finland. Logging and transportation costs, stumpage prices, tied up capital, dry matter losses and moisture content of harvested timber were considered in the study. Moisture content of artificially dried fuel chips made of fresh timber (55%) was set to 20%, 30% and 40% in the comparisons. Moisture content of fuel chips based on natural drying during storing was 40%. Transporting costs were calculated according to new higher permissible dimensions and weight limits for truck-trailers. The procurement cost calculations indicated that with artificial drying and by avoiding dry material losses of timber, it could be possible to reduce current costs of the prevailing procurement system based on natural drying of timber at roadside landings. The maximum cost level of artificial drying ranged between 1.2â3.2 â¬ MWh depending on the supply chain, moisture content and procurement volume of fuel chips. This cost margin corresponds to, e.g., organization, forwarding and transportation costs or stumpage price of delimbed stems.â1